The Impact of Postponed Fertility Treatment on the Sexual Health of Infertile Patients Owing to the COVID-19 Pandemic - Dong, Meng; Wu, Shanshan; Tao, Yanqiang; Zhou, Feifei; Tan, Jichun (Frontiers in Medicine, 2021)
Background: With the onset of the coronavirus disease 2019 (COVID-19) pandemic at the beginning of 2020, all non-essential medical treatments were suspended, including fertility treatments. As a unique group in society, patients with infertility may be more sensitive and vulnerable in the face of pressure and crisis. However, to the best of our knowledge, there have been no reports on the influence of postponed fertility treatment on the sexual health of infertile patients owing to COVID-19. Therefore, this study aimed to investigate whether postponed fertility treatment resulting from COVID-19 affects the sexual health of patients with infertility. Methods: A total of 1,442 participants were included for analysis in this large-scale study. Those with postponed fertility treatment were categorised as group A (n = 474), whereas those whose fertility treatment was not delayed were in group B (n = 968). The sexual health and psychological well-being were compared between the two groups. Results: The total Female Sexual Function Index score and five domains of female sexual function (arousal ability, vaginal lubrication, orgasm, satisfaction, and coital pain) were significantly lower in group A than those in group B (p < 0.05). The International Index of Erectile Dysfunction score and Premature Ejaculation Diagnostic Tool score were significantly higher in group A than those in group B (p < 0.05). Conclusions: Delaying fertility treatment obviously affects patients' sexual and mental health. Through a structural equation model, we observed that postponed fertility treatment mediates sexual health by regulating psychological distress and couple relationship quality.